Pembinaan Seni Batik Tulis Bagi Siswa SMA N 2 Sukoharjo - V. Kristanti Putri Laksmi (Abdi Seni, 2016)
Batik art is one of the ancestral heritage and has been determined by UN agency, UNESCO, in 2009 as an Intangible Heritage does not object or generated by the Indonesian nation, as well as no other nation possessed. Batik, a traditional cloth laden contain cultural values and philosophy of the sublime and inherited from generation to generation. Traditional batik patterns produced is a representation of local culture and stimulated by the present practice of meditation, philosophy andÂ tradition with high charisma. The problem formulation used in the Development Activities of Batik Art is how the process of making batik and how the equipment needed in the process of making batik. In addition, the Development Activities of Batik Art which was held on 19 to August 23, 2011 using themethods of lectures, discussions, andworkshops. Beside that, workshop, a direct introduction of the practice both in terms of materials, tools and techniques of batik, as well as coloring and theÂ remove wax process. Therefore, it becomes an obligation to introduce and preserve, as well as keeping to batik, are not extinct and is acknowledged to be the culture of other nations. This is what encourages the implementing development activities conducted batik in SMA Negeri 2 Sukoharjo so that younger generations can learn more about local culture is valuable and we ought to keep its existence. Key words : Batik, an intangible heritage must be preserved.Â